Academic visual identity of higher education institutions : a multimodal communication through pictorial representations - Wu, Ying Qi; Cheong, Cecilia Yin Mei (Penerbit Universiti Kebangsaan Malaysia, 2022)
Empirical studies on branding of higher education institutions have increasingly explored the notion of identity in the modern university context. The positive effects of brand communication, especially offline communication, may be well investigated, whereas few studies have analyzed how online brand communication can be realized. This study examines an under-discovered visual source, namely pictures, that performs a pivotal function to display the visual identity of Chinese universities. This study investigates the multimodal discourse of the ‘About Us’ web genre which employs pictures to portray the universities’ brand identity, and examines their meaning potentials. Drawing upon the visual grammar framework of Kress and van Leeuwen (2006), the sample for visual analysis in this study was collected from the ‘About Us’ webpages of nine elite Chinese universities (C9 League). Findings of the qualitative analysis indicate that pictures are ingeniously employed to display the virtual identity of the Chinese universities. The multifaceted brand identity of the universities may be projected through a heavy use of symbolic representations, along with a diversity of communication strategies to portray their representational meanings. The study provides information for universities to effectively use visual resources in constructing their brand identities and offering information to their target audience via the web-mediated multimodal discourses.